PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, KINERJA PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Kasus pada Perusahaan Consumer Goods yang Tercatat di Bursa Efek Indonesia Periode 2016-2020) - Maharani Karisma Wandani; Triyono Triyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to examine the effect of good corporate governance mechanisms, firm performance and firm size on earnings management. The population in this study are consumer goods companies listed on the Indonesian stock exchange for the 2016-2020 period. The sample was determined using the purposive sampling method, so that with the four predetermined sample criteria, there were 33 companies. Hypothesis testing is done by using multiple regression analysis method. The test results show that only (H5) has a significant effect on earnings management.